A heart failure program in low-income patients in Argentina (COMM-HF) - Poggio, Rosana (2024)
Objective. In low- and middle-income countries, heart failure (HF) is the leading cause of death and disability. Materials and methods. A feasibility study was conducted to assess the fidelity, reach, and adoption of an educational program led by non-medical staff to improve outpatient care for patients hospitalized with HF in the local public health system. Results. Thirty patients were included, with a mean age of 55.3 years (63.3% male). A total of 97.3% of planned home visits and 90% of scheduled phone calls were completed. Counselling modules were delivered during 90.4% of home visits, with no significant challenges reported during implementation. At the end of follow-up, there was a trend towards improved lifestyle habits, a reduction in mean heart rate (78.0 to 68.3 beats per minute; p = 0.016), a decrease in the proportion of patients in NYHA functional class III (20% to 7.4%; p = 0.041), and a slight reduction in mean body mass index (29.5 vs. 28.9; p = 0.042). Conclusions. A home-based educational program, designed to optimize outpatient management of heart failure and led by non-medical healthcare personnel, was well-received and demonstrated feasibility for implementation in low-income patients relying solely on the Argentine public health system.